Effect of some antimalarial drugs on the liver: biochemical and histopathological studies - Al-Ani, Imad Matloub Dally; Al-Janabi, Sabaa T.; Hamoudi, Salem R. (2013)
The effect of antimalarial drugs (Chloroquine, Quinine and Artemisinin on the liver has been investigated in 126 male albino rats. The animals were divided into 3 groups of 42 rats each of 36 experimental and 6 control rats. The 1st group treated with Chloroquine (10mg/ Kg/day); the 2nd group treated with Quinine (30mg/ Kg/day) and the 3rd group treated with Artemisinin (8mg/ Kg/day). Quinine and Artemisinin were injected intramuscularly, while Chloroquine was injected intraperitoneally for 14 day. The treated animals, were sacrificed after slight anaesthesia at the 1st, 4th, 6th, 9th, 12th and the 14th day. Blood was obtained from the rat tail vein after a mild prick; liver specimens were fixed in Bouin’s fixative and processed for light microscopy. The result indicated that all the used drugs causes significant increase in the activity of GOT; GPT; ACP; ACP; ALP, LDA activities with corresponding decrease in cholesterol level, total protein and blood glucose. Examination for liver sections revealed definite histological alteration in the hepatic tissue such as necrosis and degeneration of hepatocytes, congestion of the central vein, and vacuolization of cytoplasm, infiltration of inflammatory cells, dilatation and congestion of the blood sinusoids and fatty infiltration.